Abl Tyrosine Kinase Regulates Hepatitis C Virus Entry - Min, Saehong; Lim, Yun-Sook; Shin, Dongjo; Park, Chorong; Park, Jae-Bong; Kim, Seungtaek; Windisch, Marc P.; Hwang, Soon B. (Frontiers in Microbiology, 2017)
Abl is a central regulator of multiple cellular processes controlling actin dynamics, proliferation, and differentiation. Here, we showed that knockdown of Abl impaired hepatitis C virus (HCV) propagation. Treatment of Abl tyrosine kinase-specific inhibitor, imatinib and dasatinib, also significantly decreased HCV RNA and protein levels in HCV-infected cells. We showed that both imatinib and dasatinib selectively inhibited HCV infection at the entry step of HCV life cycle, suggesting that Abl kinase activity may be necessary for HCV entry. Using HCV pseudoparticle infection assays, we verified that Abl is required for viral entry. By employing transferrin uptake and immunofluorescence assays, we further demonstrated that Abl was involved in HCV entry at a clathrin-mediated endocytosis step. These data suggest that Abl may represent a novel host factor for HCV entry.